In search of an appropriate mix of taxes and subsidies on nutrients and food: a modelling study of the effectiveness on health-related consumption and mortality - Saha, S; Nordström, J; Scarborough, P; Thunström, L; Gerdtham, U-G (Elsevier, 2021)
Taxes and subsidies on foods and nutrients have the potential to promote healthier diets and thereby reduce mortality. In this study, we examine the effects of such policy instruments on Swedish public health. Specifically, we estimate the effects of food and nutrient taxes and subsidies on mortality averted and postponed in Sweden, using both demand system estimations and simulation models. We evaluate different Value Added Tax (VAT) reforms. The VAT is raised on food products that are particularly rich in saturated fat or salt and lowered on fruit and vegetables. Our models predict that an increase in the current VAT of 12% on food, to 25% VAT on products rich in saturated fat plus a 0% VAT on fruits and vegetables would result in almost 1100 deaths (95% CI: -832; -1363) averted or postponed in a year in Sweden, while the combination of a 34.4% VAT on products rich in saturated fat and a -10.4% VAT (i.e. a subsidy) on fruits and vegetables would result in almost 2100 (95% CI: -1572; -2311) deaths averted or postponed corresponding to a 4.8% reduction in diet-related annual death. Most of the deaths averted or delayed from this reform would be deaths from coronary heart disease (-1,148, 95% CI: -728; -1586), followed by stroke -641 (95% CI: -408; -887) and diet-related cancer deaths (-288, 95% CI: -11; -435). We find that health-related food taxes and subsidies improve dietary habits as well as reduce the mortality of the Swedish population. However, the effect of these reforms on different socioeconomic classes and which reforms provide the best value for money, i.e., cost-effectiveness of these reforms needs to be established first before implementation.